Effect of Graded Levels of Roselle (Hibiscus sabdariffa LINN.) Calyx Extract on Performance and Carcass Characteristic of Broiler Chickens - Omolade , Awodola-Peters; Abiola, Ajiboye Adesola; Grace, Longe Oyebiodun (International Journal of Poultry Science, 2015)
The study evaluated the effect of graded levels of the red variety of roselle (Hibiscus sabdariffa L.) calyx extract on performance and carcass characteristics of broiler chickens. A total of two hundred Arbor acres broiler birds were used for the study, these were randomly assigned to five treatments, (T1, T2, T3, T4 and T5) which had broiler chicks on water only, 2 g of roselle calyx boiled in 1 L of water for 30 min, 4 g of roselle calyx boiled in 1 L of water for 30 min, 6 g of roselle calyx boiled in 1 L of water for 30 min and 8 g of roselle calyx boiled in 1 L of water for 30 min, respectively. The birds were further randomly sub-divided into four replicates of ten birds each. The birds were given basal diets at both the starter (0-3 weeks) and finisher phases (4-6 weeks). Data obtained were subjected to ANOVA and means separated using the Duncan’s New Multiple Range Test. Result showed no significant difference in average daily fluid intake, average daily weight gain, feed intake and FCR of the birds at the starter phase. However, at the finisher phase, there was significant difference (p<0.05) in the values obtained for average daily feed intake, weight gain and feed conversion. Carcass evaluation showed birds in T5 had better breast meat weight and dressing percentage. The extract was not toxic to the birds and can be administered to broiler chickens at a graded level of 8 g of Roselle calyx boiled in 1 L of water for 30 min.